Metastasectomy Improves the Survival of Gastric Cancer Patients with Krukenberg Tumors: A Retrospective Analysis of 182 patients - Ma F; Li Y; Li W; Kang W; Liu H; Ma S; Xie Y; Zhong Y; Xu Q; Wang B; Xue L; Tian Y (Cancer Management and Research, 2019)
Fuhai Ma,1 Yang Li,1 Weikun Li,1 Wenzhe Kang,1 Hao Liu,1 Shuai Ma,1 Yibin Xie,1 Yuxin Zhong,1 Quan Xu,1 Bingzhi Wang,2 Liyan Xue,2 Yantao Tian1 1Department of Pancreatic and Gastric Surgery, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100021, People’s Republic of China; 2Department of Pathology, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing 100021, People’s Republic of ChinaCorrespondence: Yantao TianDepartment of Pancreatic and Gastric Surgery, National Cancer Center/National Clinical Research Center for Cancer/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Chaoyang District, Beijing 100021, People’s Republic of ChinaTel|Fax +86-10-87787120Email zlyytyt@163.comPurpose: There is no consensus regarding whether metastasectomy in gastric cancer patients with Krukenberg tumors (KTs) is associated with survival benefits. The aim of this study was to evaluate the treatment of KTs of gastric origin in a large series of patients and to identify prognostic factors affecting survival.Patients and Methods: All patients who were diagnosed with gastric cancer and ovarian metastases in a single medical center between January 2006 and December 2016 were identified and included. The patients were divided into two groups according to treatment modality: a metastasectomy group and a nonmetastasectomy group. Clinicopathological features and overall survival (OS) were compared between the groups.Results: In total, 182 patients were identified; 94 patients presented with synchronous KTs, and 88 developed metachronous KTs during follow-up. OS was significantly longer in the metastasectomy group than in the nonmetastasectomy group among those with synchronous (14.0 months vs 8.0 months; p = 0.001) and metachronous (14 months vs 8 months; p = 0.018) KTs. Multivariate analysis indicated that metastasectomy (hazard ratio [HR] 0.537; 95% confidence interval [CI] 0.344–0.839; p = 0.006), ascites (HR 1.523; 95% CI 1.058–2.193; p = 0.024), linitis plastica (HR 1.995; 95% CI 1.115–3.571; p = 0.020), and systemic chemotherapy (HR 0.456; 95% CI 0.280–0.742; p = 0.002) were independent predictors of OS.Conclusion: Metastasectomy combined with systemic chemotherapy should be performed in gastric cancer patients with synchronous or metachronous KTs. Metastasectomy, systemic therapy, linitis plastica, and ascites are prognostic factors for OS. Further prospective randomized studies are needed.Keywords: gastric cancer, ovarian metastasis, Krukenberg tumor, ovarian metastasectomy, survival benefit